2018
DOI: 10.3390/brainsci8070121
|View full text |Cite
|
Sign up to set email alerts
|

On the Developmental Timing of Stress: Delineating Sex-Specific Effects of Stress across Development on Adult Behavior

Abstract: Stress, and the chronic overactivation of major stress hormones, is associated with several neuropsychiatric disorders. However, clinical literature on the exact role of stress either as a causative, triggering, or modulatory factor to mental illness remains unclear. We suggest that the impact of stress on the brain and behavior is heavily dependent on the developmental timing at which the stress has occurred, and as such, this may contribute to the overall variability reported on the association of stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 200 publications
4
33
0
Order By: Relevance
“…Coadministration of quercetin (4) and piperine (1) attenuated UCMS-induced increased levels of TNF-α in mice brain [46]. Kaempferol (5) and rutin (7) decreased the release of pro-inflammatory cytokines by inhibiting AKT phosphorylation and NFκB activation [47]. Taken together, the present findings suggested that the memory-enhancing effects of KBD could be due to the improvement of antioxidant capacity of the flavonoid, phenolic acid, and triterpene glycosides, which are constituents of the plant ingredients, as well as the suppression of the HPA axis hyperactivation from the chronic stress exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coadministration of quercetin (4) and piperine (1) attenuated UCMS-induced increased levels of TNF-α in mice brain [46]. Kaempferol (5) and rutin (7) decreased the release of pro-inflammatory cytokines by inhibiting AKT phosphorylation and NFκB activation [47]. Taken together, the present findings suggested that the memory-enhancing effects of KBD could be due to the improvement of antioxidant capacity of the flavonoid, phenolic acid, and triterpene glycosides, which are constituents of the plant ingredients, as well as the suppression of the HPA axis hyperactivation from the chronic stress exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The amounts of madecassoside (2) and asiaticoside (3) found in the KBD extract were 179.35 ± 4.578 and 57.76 ± 3.003 mg/g extract, respectively. The HPLC chromatograms of ferulic acid (9), luteolin-7-O-glucoside (8), rutin (7), kaempferol-3-glucoside (6), quercetin (4), and kaempferol (5) in the KBD extract are shown in Figure S3A,B (Supplementary Materials), respectively. The amounts of ferulic acid (9), luteolin-7-O-glucoside (8), rutin (7), kaempferol-3-glucoside (6), quercetin (4), and kaempferol (5) in the KBD extract were 1.75 ± 0.128, 1.59 ± 0.464, 1.66 ± 0.289, 2.92 ± 0.063, 0.45 ± 0.039, and 0.89 ± 0.060 mg/g extract, respectively.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…MS has been reported to increase anxiety and depressive behaviors and cause cognitive disorder in adulthood, which was accomplished by alterations in HPA axis, decreased BDNF expression and altered structural and functional plasticity in the medial prefrontal cortex and hippocampus in rats and mice (Hennessy, Schreibeis, Schiml, & Deak, ; Musazzi et al, ; Seo et al, ; Tractenberg et al, ; Vetulani, ; van Zyl, Dimatelis, & Russell, ). Though most mental disorders in humans often begin to onset during adolescence (Kessler et al, ), previous studies in rodent models, however, mostly focused on the adult outcomes of early life stress (Schroeder, Notaras, Du, & Hill, ). Only a few numbers of studies have directly examined the effect on adolescents, and the findings were varied and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that adolescent female rats, not males that were exposed to social instability stress, displayed a transient increase in immobility in the forced swimming test during adolescence that diminished in adulthood (McCormick, Smith, & Mathews, 2008). The nature and severity of adverse stress, genders, and the strain of rodents are all critical elements that determine the outcomes of the effects of early life stress during adolescence (Freund, Thompson, DeNormandie, Vaccarro, & Andersen, 2013;Schroeder et al, 2018;Vetulani, 2013), and these factors may contribute to the variability of the previous results. Further studies need to clarify the roles of these factors in regulating the effect of early life stress in both adolescence and adulthood.…”
mentioning
confidence: 99%